Therapeutic Workshops and social changes in people with mental disorders - Aline Raquel de Sousa Ibiapina; Claudete Ferreira de Souza Monteiro; Delmo de Carvalho Alencar; Márcia Astrês Fernandes; Antonio Alberto Ibiapina Costa Filho (Universidade Federal do Rio de Janeiro, 2017)
ABSTRACT Objective: To analyze the impact of the therapeutic workshops and the social changes in people with mental disorders from the point of view of the experience of the workers of a Center of Psychosocial Attention. Method: A descriptive, qualitative study developed with seven professionals from a Psychosocial Care Center in a city in the Northeast of Brazil. The data production was performed through a semi-structured interview and analyzed by the Descending Hierarchical Classification, after processing in the IRaMuTeQ software. Results: Were presented in two segments: the first one portrays the reality of the work of the professionals in the Center for Psychosocial Care, while segment two emphasizes the professionals' perception about the therapeutic workshops as a tool for social reintegration. Conclusion: The use of therapeutic workshops contributes to the effectuation of social change on mental illness and social inclusion of people with psychic disorders in the daily family, in the community, encouraged by the multidisciplinary approach.